Sexual empowerment among young Black men who have sex with men - Choi, Seul Ki (J Sex Res, 2020)
Sexual empowerment represents an important HIV intervention strategy, yet limited attention has examined the multidimensional nature of sexual empowerment in prior studies. Using a sample (n = 465) of young Black men who have sex with men (MSM), we used confirmatory factor analysis (CFA) to test a multifactorial operationalization of sexual empowerment. CFA indicated that a bifactor model was best suited to characterize the sexual empowerment factor (SEF), suggesting that items for four sub-constructs (self-efficacy to refuse sexual behavior, emotional support, condom use self-efficacy, and social norms on condom use) contributed to their respective constructs, while also contributing to a latent sexual empowerment construct. We then examined the association between SEF and mental health outcomes (anxiety and depression symptoms) and safer sex intentions. SEF was negatively associated with mental health outcomes and positively associated with safer sex intentions. Ultimately, individuals with greater sexual empowerment might be better equipped to develop strategies to buffer their vulnerability to HIV. We discuss the implications of SEF as a bifactor during the design and evaluation of HIV risk-reduction interventions seeking to address sexual empowerment among MSM.